Multiculturalismo, gênero e etnografia: trajetória e contribuições fundamentais de Jean Elizabeth Jackson para a antropologia sul-americana - Patience L. Epps; Danilo Paiva Ramos; Flora Cabalzar (Journal de la Société des Américanistes)
This paper presents the trajectory of Jean E. Jackson’s principal contributions to South American anthropology within the scope of the dossier “Femmes pionnières de l’anthropologie sud-américaniste.” While we focus on her pioneering ethnographic work with the Indigenous peoples of the Colombian Vaupés, we also consider how her ethnographic perspective connects to her other lines of research on identity, indigenous movements and chronic pain patients. Our discussion draws on Jackson’s many publications and on our conversations with her in the context of several interviews. Finally, we emphasize the relevance of gender as a consistent thread throughout Jackson’s research trajectory—both as a topic of attention in her research, and as a pivot point in her own positioning as a female ethnographer.